“Every knock is a boost”. Cyber risk behaviour among Poles - Cichowicz, Ewa; Iwanicz-Drozdowska, Małgorzata; Kurowski, Łukasz (Economics and Business Review, 2021)
The purpose of this study is to evaluate the safety of individuals’ behaviour in the cyber world, especially when using financial services. The article focuses on knowledge of cybersecurity issues, cyber risk awareness and respondents’ self-assessment as potential determinants of individual behaviour. The data obtained from a survey of a representative group of Polish citizens during the second wave of the COVID-19 pandemic was analysed. Ordinal logistic regression and instrumental variable analysis confirm the existence of a positive relationship between knowledge and awareness of cyber risk and safe behaviour in the cyber world. Older generations exhibit safer behaviour which may be linked to their life experience; however, the results do not confirm that experiencing a loss due to cyber risk convinces individuals to use Internet-based solutions in a safer manner. Therefore, educational campaigns should be expanded to include cyber risk issues and tailored to the needs of various users.